The Relevance of Thematic Interpretation of the Qur'an to Contemporary Educational Leadership and Administration Practices : Case Study of PAUD KOBER Miftahul Ulum Mataram Udik - Ahmad Muhid; Elvandari Maulana (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the relevance of thematic interpretation of the Qur'an to the practice of leadership and contemporary education administration in PAUD Kober Miftahul Ulum Mataram Udik. This research uses a qualitative approach with a case study type. The research subjects included heads of institutions, teachers, and education personnel who were selected through purposive sampling techniques. Data collection techniques are carried out through observation, in-depth interviews, and documentation, while data analysis uses an interactive model that includes data reduction, data presentation, and conclusion drawn. The results of the study show that Qur'anic leadership values such as trust, justice, deliberation, and example have been implemented in real life in leadership practice. In addition, educational administration is carried out systematically by integrating the principles of planning, organizing, implementing, and evaluating based on Islamic spiritual values. The thematic interpretation of the Qur'an has proven to be relevant to the concepts of transformational leadership and modern education management, and has contributed to shaping a holistic, adaptive, and contextual model of Islamic educational leadership.